The professionalization of school leadership: conditions and challenges for the case of Argentina - Romero, Claudia (Avances en Supervisión Educativa, 2024)
Although school leadership is a key factor in improvement, as shown by international research, there is little research on the conditions of good leadership in Latin America and particularly in Argentina. In response to this gap, this paper aims to analyze the current conditions (labor, regulatory, and training) of the leadership role in Argentina and the challenges and implications for school improvement. Two recent studies conducted by the research group “Educational Leadership and School Improvement” of the Universidad Di Tella, an academic reference on the subject in the country, are analyzed and updated. They describe the conditions that regulate the work of school principals and the capacities and training needs of directors in two jurisdictions. Strong limitations were found for the professional performance of principals. The conclusions are presented as the policy challenges to develop the necessary conditions for good school leadership and with it an improvement of schools.